Makna Simbolik pada Kain Tabekh dalam Adat Istiadat Kota Subulussalam ditinjau dari Semiotika Peirce - Serli; Al Zuhri; Aulia Risky; Said Fadhlain (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Tabekh cloth is one of the traditional cultural artifacts used in various social rituals among the community of Teladan Baru Village, Rundeng District, Subulussalam City. Although its use continues to this day, the interpretation of the symbols and colors embedded in the tabekh cloth has experienced fading and shifting, and in some cases has become disconnected from the understanding of the community that sustains the tradition. This study aims to examine the symbolic meanings of the tabekh cloth through the semiotic approach of Charles Sanders Peirce, in order to explore the relationship between symbolic forms, referential meanings, and interpretive processes within the local cultural context. The findings indicate that the colors of the tabekh cloth carry symbolic meanings that represent social structures and cultural roles within the community of Teladan Baru Village. However, several decorative symbols on the tabekh cloth are no longer understood in terms of their meanings and function merely as visual ornaments without consciously recognized cultural significance. These findings underscore a disconnection between customary practices and symbolic interpretation, which has implications for the weakening of intergenerational transmission of cultural values.